The Relationship between Cigarette Smoke Exposure and Stunting among Children in the Working Area of the Pangkajene Health Center, Sidrap Regency in 2023 - Muhammad Tahir Saenong; Sulaeman; Bakhtiar; Jumiarsih Purnama; Ishak Kenre (Journal Of Nursing Practice, 2024)
Background: The major health problem currently is the smoking habit which cannot be separated from society, because smoking is considered a common thing carried out among people. As a result of this habit, cigarette smoke exposure has a direct impact on the growth and development of the children by interfering the absorption of nutrients which will later disrupt their growth and development and can influence the incidence of stunting. Purpose: This study aimed to determine the relationship between cigarette smoke exposure and the incidence of stunting among children in the working area of ​​the Pangkajene Health Center, Sidrap Regency in 2023. Method: This study was conducted from May, 25th to June, 25th 2023. This study employed a quantitative study with a cross sectional approach. A total of 45 respondents was chosen as sample in this study, using purposive sampling technique. The data collection method in this study used a questionnaire and the relationship between cigarette smoke exposure and the incidence of stunting among toddlers. Results: Exposure to cigarette smoke has a direct impact on the growth and development of their children by interfering with the absorption of nutrients in children which will later interfere with their growth and development. Conclusion: Exposure to cigarette smoke is one of the important problems that causes stunting in children because the chemicals produced can have both direct and indirect effects on children. Therefore, education is needed regarding the importance of not smoking and the negative impacts resulting from inhaling cigarette smoke.